Effects of Shrimp Aquaculture Effluent on the Habitat Suitability for Macrozoobenthos along the Situbondo Coast - Salimatul Muntafi’ah; Hartati Kartikaningsih; Fitri Candra Wardana; Wresti L. Anggayasti (Postgraduate, University of Mataram, 2026)
Shrimp aquaculture generates wastewater that may affect coastal ecosystem quality if not properly managed. This study aimed to analyze the relationship between shrimp pond effluent quality and macrozoobenthos diversity as an indicator of habitat suitability in the coastal waters of Situbondo, Indonesia. Wastewater samples were collected from pond outlet wastewater treatment plants (WWTP) in triplicate and analyzed for physicochemical parameters, including phosphate (PO₄), ammonia (NH₃), total suspended solids (TSS), biochemical oxygen demand (BOD), and pH. Macrozoobenthos samples were collected at three distances from the discharge point and analyzed using the Shannon–Wiener diversity index (H'). Data were further analyzed using multiple linear regression and Canonical Correspondence Analysis (CCA) to evaluate the relationship between environmental variables and macrozoobenthos diversity. The results showed that PO₄ concentrations at all stations exceeded the environmental quality standard (0.5 mg/L), while NH₃ concentrations exceeded the standard (5 mg/L) at four stations. TSS levels also exceeded the permitted threshold (100 mg/L) at several stations, whereas BOD and pH remained within acceptable limits. The macrozoobenthos diversity index indicated moderate diversity at stations 1 and 2 (H' ≈ 2), suggesting moderate environmental stress, while stations 3, 4, and 5 showed low diversity (H' < 1), indicating polluted conditions. Regression analysis indicated that nutrient and suspended solid parameters negatively influenced macrozoobenthos diversity, with PO₄ and NH₃ showing the strongest effects. The findings demonstrate that shrimp pond effluent can alter benthic community structure and confirm that macrozoobenthos are effective bioindicators for assessing ecological impacts in coastal ecosystems.